2024
DOI: 10.1007/s10995-023-03863-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Health Disparities Among Middle Eastern and North African Women and Children in the United States

Tiffany B. Kindratt,
Florence J. Dallo,
Kyrah K. Brown

Abstract: Introduction: Few studies have evaluated the health of Middle Eastern and North African (MENA) women and children in the United States. Objectives were to determine the odds of well-visits, preventive behaviors during pregnancy, and low birthweight among foreign-born non-Hispanic MENA women and children compared to their US-and foreign-born non-Hispanic White counterparts after adjusting for covariates (hereafter, reported as MENA and White).Methods: We analyzed 2000. Outcomes included well-woman visits (past … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Few studies have used nationally representative data to examine health among MENA children. A recent study using NHIS data found that foreign-born MENA children were more likely to have low birth weight than their White counterparts [15]; yet, to our knowledge, no studies have been published that examine the mental health patterns of MENA children on a national scale. In 2024, the OMB revised its SPD 15 guidelines and will require all national health surveys and surveillance systems that are federally funded to include a separate checkbox for MENA Americans as a minimum reporting category by 2029 [10].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Few studies have used nationally representative data to examine health among MENA children. A recent study using NHIS data found that foreign-born MENA children were more likely to have low birth weight than their White counterparts [15]; yet, to our knowledge, no studies have been published that examine the mental health patterns of MENA children on a national scale. In 2024, the OMB revised its SPD 15 guidelines and will require all national health surveys and surveillance systems that are federally funded to include a separate checkbox for MENA Americans as a minimum reporting category by 2029 [10].…”
Section: Introductionmentioning
confidence: 94%
“…Foreign-born MENA children can be compared to their US-and foreign-born White counterparts by combining responses to questions assessing race, ethnicity, and nativity status. This method has been used extensively for over 20 years to examine the health of MENA adults [12,13,[26][27][28][29][30][31][32], and the literature has recently expanded to focus on health outcomes among MENA children [15]. Our foreignborn MENA group includes non-Hispanic White children born in countries located in the Middle East and Africa.…”
Section: Strengths and Limitationsmentioning
confidence: 99%